Industry Environment: Influence On Performance Of Small-Medium Sized Enterprise In Asia-Pacific Markets - Freeman, Susan (Asian Academy of Management (AAM), 2000)
The purpose of this paper is to extend the business performance stream by examining the relationship between industry environment and business performance. This paper will assess the significance of the regulatory environment, in particular, on firm performance by examining a number of markets in the Asia-Pacific region to illustrate similarities and differences and suggest how industry structure in these markets might influence exporting firm performance. The conclusion will examine managerial implications and provide some future research directions.